2022
DOI: 10.1186/s12884-022-05265-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploring women’s experiences during childbirth in health facilities during COVID-19 pandemic in occupied palestinian territory: a cross-sectional community survey

Abstract: Introduction This study aims to assess the prevalence of mistreatment during childbirth in the occupied Palestinian territory and to explore factors associated with mistreatment. Methods A cross-sectional study of women who gave birth in the West Bank and Gaza Strip health facilities. The survey was administered over the phone to women up to 8 weeks post-partum. Data collection took place between July 2020 and March 2021. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
17
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 32 publications
3
17
1
Order By: Relevance
“…The recent study by Abu‐Rmeileh et al 8 explored the mistreatment of women during labor in five health facilities in Palestine, with 36% of participants from Gaza and the rest from the West Bank. The study reported that nearly 19% of women reported some form of violence or abuse, with women in Gaza reporting higher levels (23%) than women in the West Bank (16.4%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The recent study by Abu‐Rmeileh et al 8 explored the mistreatment of women during labor in five health facilities in Palestine, with 36% of participants from Gaza and the rest from the West Bank. The study reported that nearly 19% of women reported some form of violence or abuse, with women in Gaza reporting higher levels (23%) than women in the West Bank (16.4%).…”
Section: Discussionmentioning
confidence: 99%
“…One study has explored OV determinants in Palestine, 7 but there have been none to date exploring the experiences of women living in the Gaza Strip. A recent study explored mistreatment during delivery among Palestinian women but focused on the West Bank (four out of five included hospitals) 8 . The conditions in Gaza are reportedly more difficult than in the West Bank as Gaza faces additional restrictions on travel, a higher unemployment rate, and was the subject of at least four major military operations in the last 15 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in women’s recall and understanding of mistreatment between exit interviews and subsequent surveys may also have implications for validity metrics presented here 9 13. More recently, more evidence has been emerging using phones to conduct surveys to capture experience of care during the postnatal period 34 35. Most validation studies on quality of maternal and newborn care have used observation as a reference standard10–12 including a recent study on mistreatment measures 19.…”
Section: Discussionmentioning
confidence: 99%
“…A Cochrane intervention review reported the significance of the presence of help for women during childbirth. Women with support were less likely to have a Caesarean section, less likely to report negative feelings about their childbirth care experience, labor was shorter, and there was a reduction in unpleasant birth experiences [ 7 , 8 ].This companion can be the woman's spouse, husband, friend, healthcare professional, or family member [ 9 , 10 ] According to the absence of a labor companion, women who did not have a labor partner were more likely to experience physical abuse, feel abandoned, and have poor communication [ 10 ].…”
Section: Introductionmentioning
confidence: 99%